Standalone and grid-connected operation of single-source multilevel inverter with boosted output voltage - Mohammad Ali; Mohammad Tayyab; Adil Sarwar; Mohammad A. Abido; Muhammad Khalid (Alexandria Engineering Journal, 2024)
Multilevel inverters produce waveforms that lead to better power quality. Switched-capacitor inverters are one kind that is capable of generating boosted voltage and encourages a single-stage grid-tied inverter solution. In this paper, a four-times boost nine-level inverter with fewer switches is presented in standalone and grid-connected mode. Two switched capacitors, along with eleven switches and one diode, are employed to generate the required boosted nine-level output. The circuit modulation allows self-charging of the capacitors, with the first capacitor charging to the DC source and the second charges to twice of it by shunting it with the combination of the first capacitor voltage and the DC source. This inverter’s application can be as a solar PV microinverter due to its fewer components and small filter requirement. The topology is compared with the single-source nine-level inverters and exhibits the lowest cost of all quadruple boost inverters. The presented inverter operation is verified in Simulink and validated on the laboratory prototype. Further, to minimize the leakage current, the circuit is modified accordingly and tested in a hardware-in-the-loop environment.